THE EFFECTIVENESS OF DIFFERENT METHODS FOR DETECTING EARLY DENTAL CARIES - Hanan Omar Basmeer, Aishah Hassan Magrashi , Aminah Ali Al Yami , Ashwaq Awad Mayuf Alanazi, Mohammad Haif Saeed Alqhtani, Abdulaziz Naser Abdulaziz Al Munyif, Mohammed Muflih Mohammed Alrabie, Alaa Ibrahim Aldhuwalia, ,; Maryam Mohammed Ahmed Alqabi, Hassan Hussain Alnasser, Hussain Khalid Alattiah, Dalal Nasser Alharbi, Mosheera Suliman Salman Almutairi, Akram Hussein Marzouki, Aminah Saeed Hamad Almutairi, (Chelonian Research Foundation, 2022)
The objective was to evaluate the data about the effectiveness of several methods for detecting early tooth decay in living organisms. A systematic search was conducted across five databases, including published research. The search phrases used were "early caries" and "caries detection." The inclusion criteria were studies that examined the accuracy of diagnostic tests for early diagnosis of caries in both permanent and primary teeth. An evaluation of potential bias was conducted using the QUADAS-2 instrument. We conducted the process of research selection, data extraction, and risk-of-bias evaluation in duplicate. The review process was filed in advance in the Open Science Framework. When examining the occlusal surfaces of permanent teeth, the DIAGNOdent Pen (DD Pen) showed a high sensitivity range of 0.81-0.89, as determined by histologic examination. This was followed by ICDAS-II with a sensitivity range of 0.62-1, DIAGNOdent (DD) with a sensitivity range of 0.48-1, and bitewing radiography (BW) with a sensitivity range of 0-0.29. The Se and Sp values exhibited variability, which may be attributed to the diversity in the settings of separate investigations. Clearly, definitive judgments cannot be made, and other diagnostic methods should be used in addition to clinical evaluation. For permanent teeth, the use of digital radiography (DD) on the biting surfaces and bitewing radiography (BW) on the areas between teeth may improve visual assessment. DD Pen may be used as an additional tool on all surfaces of primary teeth. Keywords: Caries identification, Initial caries, Developing caries, Adult teeth, Baby teeth